2020
DOI: 10.3389/fphar.2020.581098
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic Receptors in Neurotransmission, Synaptic Plasticity, and Cognition

Abstract: a 1-adrenergic receptors are G-Protein Coupled Receptors that are involved in neurotransmission and regulate the sympathetic nervous system through binding and activating the neurotransmitter, norepinephrine, and the neurohormone, epinephrine. There are three a 1-adrenergic receptor subtypes (a 1A , a 1B , a 1D) that are known to play various roles in neurotransmission and cognition. They are related to two other adrenergic receptor families that also bind norepinephrine and epinephrine, the band a 2-, each wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 336 publications
(432 reference statements)
2
70
0
Order By: Relevance
“…While one of these studies ( Hertz et al, 2010 ) argues for astrocyte-specific expression of α1-NAR, it should be noted that other single cell RNA sequencing studies have found that (inter)neurons also express significant amounts of the various α1-NAR transcripts ( Figure 1C ) ( Zhang et al, 2014 ; Zeisel et al, 2015 ). The majority of single cell transcriptome studies, however, are in agreement that α1A-NAR and α1B-NAR appear to be the main α1-NAR subtypes expressed in cortical astrocytes, with α1D-NAR found in much lower amounts, effectively confirming earlier work using transgenic models and radioligand binding ( Perez, 2020 ). Two recent studies independently generated transgenic mouse lines with LoxP sites flanking Adra1a , allowing conditional deletion of the gene in astrocytes by crossing to appropriate Cre drivers.…”
Section: Noradrenergic Receptors In the Cnssupporting
confidence: 81%
See 1 more Smart Citation
“…While one of these studies ( Hertz et al, 2010 ) argues for astrocyte-specific expression of α1-NAR, it should be noted that other single cell RNA sequencing studies have found that (inter)neurons also express significant amounts of the various α1-NAR transcripts ( Figure 1C ) ( Zhang et al, 2014 ; Zeisel et al, 2015 ). The majority of single cell transcriptome studies, however, are in agreement that α1A-NAR and α1B-NAR appear to be the main α1-NAR subtypes expressed in cortical astrocytes, with α1D-NAR found in much lower amounts, effectively confirming earlier work using transgenic models and radioligand binding ( Perez, 2020 ). Two recent studies independently generated transgenic mouse lines with LoxP sites flanking Adra1a , allowing conditional deletion of the gene in astrocytes by crossing to appropriate Cre drivers.…”
Section: Noradrenergic Receptors In the Cnssupporting
confidence: 81%
“…Indeed, NAR expression profiles remain a matter of debate and are only being slowly clarified. This is probably due to the difficulties of obtaining reliable antibodies for adrenoreceptors, as well as the shortcomings of genetic models generally used to study this question (in which overexpression of reporter genes, driven by a fragment of the endogenous promoter, might not precisely recapitulate the cellular expression profile of a given NAR; Perez, 2020 ).…”
Section: Noradrenergic Receptors In the Cnsmentioning
confidence: 99%
“…To investigate the potential correlates of meso-scale integration, we interrogated the neurotransmitter receptor signature of each region of the brain. We used the Allen Brain Atlas micro-array atlas (http://human.brain-map.org/) to identify the regional signature of genetic expression of two subtypes of adrenergic receptor (ADRA1A and ADRA2A) that have been a priori related to cognitive function and attention [45], and are the most abundant adrenergic subtypes expressed in the cerebral cortex [46]. To test for specificity, we also evaluated two muscarinic receptor densities (Chrm1 and Chrm2) and two dopaminergic receptor densities (Drd1 and Drd2).…”
Section: Methodsmentioning
confidence: 99%
“…The Locus Coeruleus (LC) is the main noradrenergic nucleus and the main site for the synthesis of NE in the brain. The LC-NE system consists of neurons that project to different brain regions and supplies NE to the cortex, hippocampus, striatum, amygdala, cerebellum, basal forebrain, and the hypothalamus [ 70 ]. LC, NE, and adrenergic receptors (ARs) play a significant role in AD pathology and in Aβ peptides production and secretion.…”
Section: Norepinephrine Adrenergic System and Alzheimer’s Diseasementioning
confidence: 99%
“…This study then suggests that α1 ARs are activated in AD and that this activation is often manifested by malfunctioning of NE neurotransmission in the hippocampus. Perez, 2020 described the role of α1 ARs in short-term and long-term synaptic plasticity in different brain regions such as the hippocampus, neocortex and the PFC, regions adversely affected in AD patients [ 70 ].…”
Section: Norepinephrine Adrenergic System and Alzheimer’s Diseasementioning
confidence: 99%